Large Random Matrices: Lectures on Macroscopic Asymptotics École d'Été de Probabilités de Saint-Flour XXXVI - 2006 - Guionnet, Alice (École d'Été de Probabilités de Saint-Flour ;, 2009)
Random matrix theory has developed in the last few years, in connection with various fields of mathematics and physics. These notes emphasize the relation with the problem of enumerating complicated graphs, and the related large deviations questions. Such questions are also closely related with the asymptotic distribution of matrices, which is naturally defined in the context of free probability and operator algebra. The material of this volume is based on a series of nine lectures given at the Saint-Flour Probability Summer School 2006. Lectures were also given by Maury Bramson and Steffen Lauritzen.